Predictive Validity of the DYRA and SAFVR: New Zealand Police’s Family Violence Risk Assessment Instruments - Jolliffe Simpson, Apriel D. (Criminal justice and behavior, 2021)
Rapid access to accurate risk assessment information is essential for effective police responses to family violence (FV) calls for service. This study describes the predictive validity of the Dynamic Risk Assessment (DYRA) for family violence and Static Assessment of Family Violence Recidivism (SAFVR), currently in use by the New Zealand Police. We used 1,817 police reports of FV episodes to predict recurrence (i.e., repeat call for police service) over three follow-up periods. Regardless of follow-up, the DYRA and SAFVR each displayed poor ability to discriminate between episodes with and without a recurrence. Both instruments substantially over-predicted recurrence and performed relatively consistently across subsamples (e.g., intimate partners vs. other family relationship; aggressor gender, ethnicity, age). The especially poor performance of the DYRA suggests further research on dynamic risk factors and their contribution to police responses for FV is needed to make these instruments more useful for agencies working with families.